Answer:
2ab(3b^2+2a+4)
Step-by-step explanation:
6ab^3 + 4a^2b + 8ab
2*3*a*b*b^2 +2*2*a*a*b +2*2*2*a*b
Factor out the common terms
2ab( 3*b^2 +2*a +2*2)
2ab(3b^2+2a+4)
3x - 2y = 7
-2y = -3x + 7
y = 3/2x - 7/2....slope of this line is 3/2. A perpendicular line will have a negative reciprocal slope. All that means is " flip " the slope and change the sign. So the slope we need is -2/3 (see how I flipped the slope and changed the sign)
y = mx + b
slope(m) = -2/3
(-3,-2).....x = -3 and y = -2
now we sub and find b, the y int
-2 = -2/3(-3) = b
-2 = 2 + b
-2 - 2 = b
-4 = b
so ur perpendicular equation is : y = -2/3x - 4 <==
Use the Quadratic formula,
x= -b +/- sqrt(b^2-4ac)
-------------------------
2a
x= 4 +/- sqrt(16+12)
----------------------
-6
x = 4+/- sqrt(28)
---------------
-6
x = 4 +/- 2*sqrt(7)
------------------
-6
x= 2(2+/- sqrt(7))
------------------
2(-3)
x= 2+/- sqrt(7)
--------------
-3
Answer:
7.71 is the answer hope you get it